2005
DOI: 10.1111/j.1365-2893.2005.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of glycosaminoglycan‐binding sites within hepatitis C virus envelope glycoprotein E2*

Abstract: Heparan sulphate is one of the candidate receptors for hepatitis C virus (HCV). Envelope glycoproteins of HCV have been proposed to be responsible for recognition and binding with cell receptors. They are characterized by great genetic polymorphism. In this study the mapping of regions with glycosaminoglycan-binding properties within HCV envelope proteins has been undertaken. We prepared a set of overlapping peptides corresponding to conserved regions of these envelope proteins and analysed them by solid phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…, present in all Lospins (not shown). These patterns showed similarity to glycosaminoglycan (GAG) binding sites; XBnXmB (where X and B=non-basic and basic residues respectively, n=1, 2, or 3 basic residues and m=1 or 2 non-basic residues (Munoz and Linhardt, 2004;Olenina et al, 2005 , which are important in heparin binding (Olson et al, 2002;Schedin-Weiss et al, 2004;dela Cruz, 2006). To further examine the possibility of the basic residues on ␣-helix D of L5 and L13-16 being involved in heparin (GAG) binding activity, we calculated surface electrostatic potentials for L5 and L13-16 models.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…, present in all Lospins (not shown). These patterns showed similarity to glycosaminoglycan (GAG) binding sites; XBnXmB (where X and B=non-basic and basic residues respectively, n=1, 2, or 3 basic residues and m=1 or 2 non-basic residues (Munoz and Linhardt, 2004;Olenina et al, 2005 , which are important in heparin binding (Olson et al, 2002;Schedin-Weiss et al, 2004;dela Cruz, 2006). To further examine the possibility of the basic residues on ␣-helix D of L5 and L13-16 being involved in heparin (GAG) binding activity, we calculated surface electrostatic potentials for L5 and L13-16 models.…”
Section: The Journal Of Experimental Biologymentioning
confidence: 99%
“…Further studies suggested that the hypervariable region 1 (HVR1) of E2 binds with heparin, and the infectivity of the VSV/HCV pseudotype is diminished in the presence of soluble GAGs or decreased after the enzymatic removal of heparinlike GAGs from the cell surface (7). A different group of investigators have suggested that HCV particles can be efficiently purified from patient sera by using heparin, and GAG binding sites are located within E2 (27,32).…”
mentioning
confidence: 99%
“…Results of genome sequence analysis are applied in the studies directed to the development of vaccines against viral (Hepatitis C [71,72], SARS [9][10][11][12]) and bacterial (Tuberculosis [73,74], Syphilis [75], Meningitis [66]) infections. Moreover, genomics studies enable to design experimental vaccines against parasite infections (Malaria [76,77], Chlamydiosis [78,79]), which have been out of vaccine studies for a long time.…”
Section: Prediction Of the Functional Features Of Proteins Based On Tmentioning
confidence: 99%